AN ANALYSIS OF MONITORING PRACTICES OF SUPERVISION RESULTS FOLLOW-UP (TLHP) - Fitriani, Nanda Alivia; Wijayanti, Anita (EQUITY, 2025)
This research analyzes the flow of TLHP monitoring implementation by APIP based on existing regulations. Then identify the obstacles faced and what policies APIP has implemented in the process of accelerating the completion of audit findings using Edward's Theory of Policy Implementation III. Data and information were obtained by conducting observations, interviews and documentation with two heads of division and two implementing employees at APIP "X" in Province "X" which was determined using purposive judgment. This research found that the main obstacles in completing TLHP were policy weaknesses, limited resources, and weak bureaucratic structures so that coordination between auditors and auditees was not yet effective. The results of this research also show that there are still obstacles for which there is no policy to improve, namely a lack of resources and a weak bureaucratic structure. Apart from that, it is important to add basic regulatory elements to Edward III's Implementation Theory so that policy implementation is more focused. This research has implications for the development of Edward's Theory of Policy Implementation III and provides necessary recommendations for APIP in the process of accelerating the completion of audit findings. Keywords: Internal Supervision; TLHP Monitoring; Edward's Theory of Policy Implementation III.